Friction Stir Welding of Aerospace Alloys (Journal of Mechanical Engineering, 2019)
Friction Stir Welding (FSW) is a solid state joining process which possesses a great potential to revolutionise the aerospace industries. Distinctive materials are selected as aerospace alloys to withstand higher temperature and loads. Sometimes these alloys are difficult to join by a conventional welding process but they are easily welded by FSW process. The FSW process in aerospace applications can be used for: aviation for fuel tanks, repair of faulty welds, cryogenic fuel tanks for space vehicles. Eclipse Aviation, for example, has reported dramatic production cost reductions with FSW when compared to other joining technologies. This paper will discuss about the mechanical and microstructure properties of various aerospace alloys which are joined by FSW process.